Bioactive Compound and Fatty Acid Profile Analysis of Cold-pressed Flavor Oil - Antonius Yulianto Djoko Pamungkas; Jose Abi Shalom Harris Purnama; Yohanes Alan Sarsita Putra; Lindayani -; Dyah - Wulandari (JFCN: Journal of Food, Culinary, and Nutrition, 2025)
Flavor oil is an innovative cooking oil mixed with herbs, spices, and fruit extract oils. This product innovation uses sunflower oil obtained through a cold press extraction method, which preserves the nutrients of the raw ingredients. In this study, there are four sunflower oil-based flavor oil variants: F1 (garlic oil), F2 (F1 + rosemary oil), F3 (F1 + red curry oil and chilli), and F4 (lemon oil, mandarin orange oil, and pineapple oil). Fatty acid content was analyzed using a Chromatography Ionized Detector (GC-FID). In contrast, micronutrients (vitamins A, E, D3, and minerals) were analyzed using Inductively Coupled Plasma Optical Emission Spectrometry (ICP-OES), Performance Liquid Chromatography-Photodiode Array (HPLC-PDA), and Liquid Chromatography Tandem-Mass Spectrometry (LC-MS/MS). Research results show that all four products contain higher levels of unsaturated than saturated fatty acids. Oleic and linoleic acids dominate the composition of the unsaturated fatty acids. These products also contain vitamins A (32.81 - 1354.88 mcg/100g), E (16.49 - 30.55 mg/100g), and D3 (0 - 0.48 mcg/100g). Mineral content includes potassium (2.59 - 4.6 mg/100g), magnesium (0.29 - 0.44 mg/100g), zinc (0.06 - 0.12 mg/100g), and calcium (0.33 - 1.39 mg/100g). Based on literature studies, these products' fatty acids and micronutrients play a role in preventing cardiovascular diseases and high blood pressure, making them suitable as practical cooking oils that support a healthy lifestyle.